The Helping Behavior of Senior and Vocational High School Students Based on the Values of Pancasila in Pemalang Regency - Priyono, Dedit; Z. Mansoor, Alvanov; R. Mutiaz, Intan (Udayana Journal of Social Sciences and Humanities; Vol 2 No 1 (2018): UJoSSH, Feburary 2018DO - 10.24843/UJoSSH.2018.v02.i01.p04, 2018)
The decline in a social relationship has led people, particularly teenagers, to an unwillingness to help others. Therefore, there needs such an effort to help teenagers realize the importance of helping others. One possible effort is to hold a character building program. In this case, the writer involves Pancasila as the fundamental principle of the program to relate its values to the helping behavior the teenagers might show. Accordingly, this study focuses on finding the helping behavior related to the values contained in the Sila of Pancasila shown by the teenagers. This descriptive-qualitative study uses Focus Group Discussion (FGD) and literature study methods to collect data. From the research, the writer finds Sila 2 Kemanusiaan Yang Adil dan Beradab fits the helping behavior shown by the teenagers the most. The helping behavior shown relates, particularly, with the following values of Pancasila, i.e., "To recognize equality both in rights and responsibility, to uphold the values of humanity," and "To promote fairness to others." Nevertheless, teenagers have not shown yet the one related with "To practice tolerance and show empathy."